Identification and Analysis of MHCⅡ Genes in Wuzhishan Pigs - LIU Yuanyuan; XIN Wenshui; CHAO Zhe; CAO Zongxi; CAI Yifei; LI Qiang; LI Lingwei; LIU Guangliang (Shiyan dongwu yu bijiao yixue)
ObjectiveTo obtain the gene sequences of major histocompatibility complex (MHC ) Ⅱgenes of Wuzhishan pigs, analyze their genetic information, and explore the biological functions of their MHC system.MethodsSpleen samples were collected from 3 adult male Wuzhishan pigs. Primers were designed according to MHCⅡ gene sequences, and the coding sequences of Wuzhishan pig MHCⅡ genes were amplified by RT-PCR. Sanger sequencing was performed to determine the full-length sequences. Bioinformatics tools were employed to analyze the physicochemical properties, phylogenetic relationships, conserved motifs, structural domains, chromosomal localization, and syntenic relationships of these genes.ResultsEight MHCⅡ genes were identified in Wuzhishan pigs, designated as SLA-DRA, SLA-DQA, SLA-DQB, SLA-DRB, SLA-DOB, SLA-DMB, SLA-DMA and SLA-DOA. The full-length sequences of these genes were determined by Sanger sequencing and subsequently deposited in GenBank under accession numbers PQ182796, PQ182797, PQ182798, PQ182799, PQ182800, PQ182801, PQ182802, and PQ164779. Phylogenetic analysis showed that the six MHCⅡ genes of Wuzhishan pigs clustered separately from their counterparts in Duroc, Meishan, Large White, and Bama pigs, indicating distinct evolutionary trajectories. Bioinformatics analysis demonstrated that most MHC Ⅱ proteins were hydrophobic, with molecular weights ranging from 27 700 to 30 000 Da. Genes within the same subregion shared conserved motifs. Specifically, four MHCⅡ proteins encoded by SLA-DQB, SLA-DRB, SLA-DOB, and SLA-DMB contained the MHCⅡβ conserved domain, while those encoded by the genes SLA-DRA, SLA-DQA, SLA-DMA, and SLA-DOA contained the MHCⅡα conserved domain. The eight MHCⅡ genes were scattered along the long arm of chromosome 7 in the Wuzhishan pigs, exhibiting syntenic relationships with three human genes and five Duroc pig genes.ConclusionThe MHCⅡ genes of Wuzhishan pigs may possess a unique evolutionary origin.